The Factors Related to Anemia in Pregnant Women - Aulia, Yenny; Siauta, Jenny Anna; Ferdinan, Jacklean; Dahlan, Febry Mutiariami (Indonesian Journal of Global Health Research, 2024)
As indicated by information from the East Nusa Tenggara Provincial Health Office in 2018, 46.2% of pregnant women experience anemia. According to data from the East Nusa Tenggara Provincial Health Office in 2018, 46.2% of pregnant women experienced anemia. Data from the Kupang District Health Office in 2021 recorded that 36.2% of pregnant women with anemia. To determine the factors associated with the incidence of anemia among pregnant women in the Naibonat Hospital, Kupang Regency. Methodology : The exploration configuration utilized a cross sectional plan. The example in this study was 74 pregnant ladies who had their pregnancy checked in Naibonat Hospital utilizing a basic arbitrary inspecting technique. The examination instrument utilized was a survey. Bivariate investigation had been finished by the Chi Square test. Out of 74 pregnant ladies who experienced paleness which was 63.5%, SEZ was 75.7%, had a propensity for consuming espresso was 59.5%, stuck to consuming Fe tablets was 52.7%, pregnancy stretch was not in danger was 54.1%, had an absence of information about pallor was 52.7%. There was a critical connection between espresso utilization (P = 0.003), adherence to Fe tablets (P = 0.000), gestational distance (P = 0.001), information on pregnant ladies (P = 0.003) and the occurrence of frailty in pregnant ladies, and there was no a huge connection between the frequency of iron deficiency in pregnant ladies with nourishing status (P = 0.056). There was a huge connection between espresso drinking propensities, adherence to polishing off Fe tablets, pregnancy stretch, information and the frequency of paleness in pregnant ladies. There was no huge connection between healthful status and the occurrence of paleness. Suggestion : Increment the information on pregnant ladies about the significance of taking an interest in family arranging programs to have the option to deal with the distance between the current pregnancy and the past pregnancy, and the risks of a pregnancy that is excessively near the past pregnancy.